Impact of p16-overexpression on overall and progression-free survival outcomes in oral cavity squamous cell carcinomas: A semi-national, population-based study. (December 2020) - Schneider, Katrine; Jakobsen, Kathrine K.; Jensen, Jakob S.; Wessel, Irene; Christensen, Anders; Specht, Lena; Lelkaitis, Giedrius; Mirian, Christian; Buchwald, Christian v.; Grønhøj, Christian
Highlights: From 575 patients with oral cavity cancer 13% (n = 69) had p16-positive tumors. p16-positivity showed no significant influence on overall or progressions-free survival outcomes. p16-status is a poor tool in prognostication of oral cavity cancer patients. Routine p16 testing should be reconsidered in terms of cost-effectiveness. Abstract: Objectives: Human papillomavirus infection and p16-overexpression is a principal cause and favorable prognostic factor for oropharyngeal squamous cell carcinomas but the value as prognostic marker in oral cavity squamous cell carcinomas (OSCC) is undetermined. Materials and methods: All patients diagnosed with OSCC in Eastern Denmark in the period 2008–2014 were enrolled. Survival estimates were evaluated as overall survival (OS) and progression free survival (PFS) by Kaplan-Meier survival curves and multivariate Cox-regression analyses. Results: We included 575 patients from which 13% (n = 69) had p16-positive tumors. The 5-year OS were 55% and 62% for the p16-negative and p16-positive patients, respectively, and the 5-year PFS were 48% and 50%. In a multivariate survival analysis, p16-positivity showed no significant influence on OS (HR: 1.06 [0.67–1.70], p = 0.79) and PFS (HR: 1.11 [0.76–1.63], p = 0.58). Conclusion: In this population-based cohort of non-selected OSCC patients, we found no difference in survival outcomes when stratified on p16-overexpression status.